Studi tentang Program Operasi Danau Jatiluhur Jernih untuk Mendukung Revitalisasi Waduk Jatiluhur - Riza Rizkiah (Sainteks: Jurnal Sain dan Teknik, 2019)
Jatiluhur Reservoir is one of the largest reservoirs in West Java which has many functions, one of which is for aquaculture with the KJA system. But along with the development of KJA activity in the Jatiluhur Reservoir it has become one of the factors causing the decline in water quality of the Jatiluhur Reservoir. Therefore the Purwakarta Regency government made a program called Operation Jatiluhur Jernih Lake through the Decree of the Regent of Purwakarta No.523.31.05 / Kep.286-DLH / 2017. This program had a purpose to curb a number of cageculture in Jatiluhur Dam. The purpose of this study was to analyze the effectiveness of the program as an effort to save the condition of reservoir water and to analyze the impact of the program to the sosio-economic condition of the farmer. The methode that used in this study was quantitavie methode based on the effectivity value from the quisioner and the qualitative method by analyzing data from interview. the results of this study indicate that the Jatiluhur Lake Operations program is running quite effectively with the acquisition of a score of 60.37%, which means this program has a pretty good value in efforts to save the water conditions of the Jatiluhur reservoir. But on the other hand this program has a significant impact, especially on the socio-economic conditions of farmers such as decreasing income levels, rising potential for unemployment, increasing levels of difficulty in fulfilling the needs of life, and also reducing the supply of fish in the Jatiluhur Reservoir